Thermal ignition in a reactive viscous plane-Poiseuille flow: a bifurcation study - Makinde, Oluvole D. (Computer Assisted Methods in Engineering and Science; Vol 12 No 1 (2005), 2022)
Thermal ignition for a reactive viscous flow between two symmetrically heated walls is investigated. The second order nonlinear boundary value problem governing the problem is obtained and solved analytically using a special type of Hermite-Padé approximation technique. We obtained very accurately the critical conditions for thermal ignition together with the two solution branches. It has been observed that an increase in viscous heating due to viscous dissipation can cause a rapid decrease in the magnitude of thermal ignition critical conditions.